2017
DOI: 10.1093/geront/gnx194
|View full text |Cite
|
Sign up to set email alerts
|

Using Contact Theory to Assess Staff Perspectives on Training Initiatives of an Intergenerational Programming Intervention

Abstract: Contact theory provided a useful framework to understand the researcher-practitioner partnership. Researchers should plan for partnerships that: (a) are supported by authority figures, including staff and participants, (b) utilize a shared expertise approach where partners have equal group status, (c) involve close cooperation; (d) align research and program goals, and (e) foster positive communication through frequent contact using practitioners' preferred methods and including in-person contact. We recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Following the integration of the children into the garden sessions, the research team observed and noted the developing intergenerational interactions between participants in the garden. We were aware of a body of literature supporting the benefit of intergenerational programming (Heyman, Gutheil, & White-Ryan, 2011;Weaver, Naar, & Jarrott, 2017) and were interested to learn more about this aspect of Planting Seeds. Analysis of our interview transcripts revealed a notable benefit for both child and adult participants in regard to fostering positive intergenerational relationships between children and adults participating in Planting Seeds.…”
Section: Nurturing Intergenerational Relationshipsmentioning
confidence: 99%
“…Following the integration of the children into the garden sessions, the research team observed and noted the developing intergenerational interactions between participants in the garden. We were aware of a body of literature supporting the benefit of intergenerational programming (Heyman, Gutheil, & White-Ryan, 2011;Weaver, Naar, & Jarrott, 2017) and were interested to learn more about this aspect of Planting Seeds. Analysis of our interview transcripts revealed a notable benefit for both child and adult participants in regard to fostering positive intergenerational relationships between children and adults participating in Planting Seeds.…”
Section: Nurturing Intergenerational Relationshipsmentioning
confidence: 99%
“…Seefeldt, 1987;Weaver et al, 2019). Other intergenerational scholars have addressed the need for authority figures to demonstrate support for IGP, such as by providing adequate materials and space for programing (Norouzi et al, 2019) and giving program leaders dedicated time to prepare for, monitor, and document the IGP (Weaver et al, 2019). Cohen-Mansfield and Muff's findings echo the critical need for this contact theory tenet to characterize Tel Aviv IGP.…”
mentioning
confidence: 93%
“…They offer synchronous and asynchronous training that covers topics such as planning IGP and how to connect generations through the arts. Experience would suggest that extensive synchronous training may be difficult to achieve for all stakeholders (Weaver et al, 2019), yet organizations may offer general training for all participants and focused training for a subset of stakeholders, such as program leaders. Access to free, asynchronous online training delivered in discrete units can increase the feasibility of stakeholders, particularly younger persons and program leaders, completing training.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Weaver et al [31] address sustainability as "a common barrier to Intergenerational Practice" (p. 3) and identify a range of critical components to enhance IP sustainability: on-site presence, open communication and positive intergroup contact (based on reciprocity and interdependence) among partners, relationship-building, cross-training, best practice use, and documentation. According to these authors, following the tenets of contact theory may equally help to implement the IP, and the use of principles from community-based participatory action research may foster IP sustainability too.…”
Section: Introductionmentioning
confidence: 99%